2016
DOI: 10.1007/s11682-016-9605-7
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety symptoms are associated to disruption of default mode network in subacute ischemic stroke

Abstract: Depression and anxiety symptoms are common after stroke and associated to reduction in quality of life and poor physical and social outcomes. The Default Mode Network (DMN) plays an important role in the emotional processing. We investigated whether these symptoms are associated to a disruption of DMN functional connectivity in the first month after stroke. Thirty-four subacute ischemic stroke patients were submitted to: 1) behavioral assessment through Beck Depression Inventory (BDI), Beck Anxiety Inventory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 61 publications
6
31
0
3
Order By: Relevance
“…Fornito et al (43) reported that functional neuronal network disruption may be more critical than lesion location to explain PSA. Vicentini et al (12) reported that PSA was not associated with infarct location but correlated with disruption of the default mode network (DMN) in the brain. Accordingly, examining the effects of the integrity of brain networks or neural circuits rather than a single location on PSA might be another direction for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fornito et al (43) reported that functional neuronal network disruption may be more critical than lesion location to explain PSA. Vicentini et al (12) reported that PSA was not associated with infarct location but correlated with disruption of the default mode network (DMN) in the brain. Accordingly, examining the effects of the integrity of brain networks or neural circuits rather than a single location on PSA might be another direction for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors related to PSA include depression (57), cognitive impairment (5, 8), fatigue (9), age (1012), female sex (10, 12), lesion location (13, 14), and sleep disturbance (9, 15), indicating PSA might be multifactorial. Apart from stress due to acute ischemic stroke, the biological mechanisms of PSA should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Chand et al (2017), also found abnormal interactions among the SN, DMN, and CEN in subjects with mild cognitive impairments. Recent research suggest that that depression and anxiety are associated with alterations in the DMN, expanding the role of DMN in emotion processing (Vicentini et al, 2017), as FC of left dAI-right DLPFC not only showed positive correlation with SDMT performance, but also negative correlation with SAS scores. Combing the hyperperfusion in the insula, we used an “inefficient high-order control” theory to illustrate this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The superior frontal gyrus and middle frontal gyrus are both involved in emotional disorders and higher cognitive functions (Tucker et al, 1981; Mayberg, 1994). Using modern neuroscience technologies like proton magnetic resonance spectroscopy (Kumar et al, 2002), DTI (Yang et al, 2015b), resting-state electroencephalogram (EEG) (Zhang et al, 2015), and resting-state functional MRI (rs-fMRI) (Vicentini et al, 2017), researchers have found that the frontal lobe of depressive or PSD patients also has white matter biochemical abnormalities, loss of white matter integrity, decreased EEG complexity, and increased functional connectivity. The anatomical basis behind these findings might include the extensive connections between frontal cortex and structures related to emotional behavior, such as the amygdala, basal ganglia, and thalamus (Soares and Mann, 1997).…”
Section: Discussionmentioning
confidence: 99%